Effects of thyroid-stimulating hormone suppression after thyroidectomy for thyroid cancer on bone mineral density in postmenopausal women: a systematic review and meta-analysis. Issue 5 (13th May 2021) - Kwak, Donghee; Ha, Jane; Won, Yousun; Kwon, Yeongkeun; Park, Sungsoo
Abstract : Objectives: We assessed thyroid-stimulating hormone (TSH) suppression effects on bone mineral density (BMD) in postmenopausal women who underwent thyroidectomy. Data sources: PubMed, EMBASE, Cochrane Library, Web of Science and SCOPUS were searched from inception to 24 February 2021. Study selection: Case-control studies were included. Data extraction and synthesis: Two authors independently reviewed the studies, extracted the data and performed meta-analysis of eligible studies. Research design and methods: Studies evaluating BMD in postmenopausal women with thyroid cancer who had thyroidectomy and levothyroxine therapy were included. Differences in BMD were presented as standardised mean differences (SMDs). Meta-analyses were conducted using a random-effects model. Results: Analysis of 16 case-control studies (426 patients and 701 controls without thyroid cancer) showed that stringent TSH suppression (TSH <0.10 mIU/L) after thyroidectomy had deleterious effects on the BMD of the lumbar spine in postmenopausal women compared with controls (SMD −0.55; 95% CI −0.99 to −0.10; I 2 =75.8%). There was no significant difference in patients with moderate TSH suppression (TSH 0.10–0.49 mIU/L). TSH suppression in postmenopausal women was not significantly associated with lower femoral neck BMD. Subgroup analysis of the lumbar spine showed that the association between stringent TSH suppression and lower BMD was consistent among studies with >10 years of follow-up (SMD −0.32; 95% CI −0.50 to −0.14). Subgroup analysis of the femoral neck showed that total thyroidectomy was related to detrimental effects on the BMD of the femoral neck (SMD −0.60; 95% CI −0.89 to −0.31; I 2 =90.4%), but near-total thyroidectomy was not (SMD 0.00; 95% CI −0.30 to 0.30; I 2 =55.6%). Conclusions: Stringent TSH suppression had deleterious effects on the BMD of the lumbar spine after thyroidectomy in postmenopausal women. Further studies are needed to determine whether stringent TSH suppression after thyroidectomy increases the fracture risk.